2018
DOI: 10.1103/physrevb.97.161404
|View full text |Cite
|
Sign up to set email alerts
|

Dirac dispersion generates unusually large Nernst effect in Weyl semimetals

Abstract: Weyl semimetals expand research on topologically protected transport by adding bulk Berry monopoles with linearly dispersing electronic states and topologically robust, gapless surface Fermi arcs terminating on bulk node projections. Here, we show how the Nernst effect, combining entropy with charge transport, gives a unique signature for the presence of Dirac bands. The Nernst thermopower of NbP (maximum of 800 VK -1 at 9 T, 109 K) exceeds its conventional thermopower by a hundredfold and is significantly la… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
101
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 112 publications
(105 citation statements)
references
References 34 publications
4
101
0
Order By: Relevance
“…Upon cooling, a xx exhibits a sign reversal and reaches a minimum value of À20 mV K À1 near 100 K. In a previous work, Watzman et al reported a minimum a xx of about À10 mV K À1 in single crystal NbP. 22 The deviation of a xx between singlecrystalline and polycrystalline NbP might originate from the difference of the direction of measurement and slight change of the position of Fermi level induced by slightly different Nb/P View Article Online stoichiometry. Overall, the obtained a xx in both polycrystalline and single crystal NbP is about one order of magnitude lower than that of good TE materials, indicating the bad TE properties of NbP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon cooling, a xx exhibits a sign reversal and reaches a minimum value of À20 mV K À1 near 100 K. In a previous work, Watzman et al reported a minimum a xx of about À10 mV K À1 in single crystal NbP. 22 The deviation of a xx between singlecrystalline and polycrystalline NbP might originate from the difference of the direction of measurement and slight change of the position of Fermi level induced by slightly different Nb/P View Article Online stoichiometry. Overall, the obtained a xx in both polycrystalline and single crystal NbP is about one order of magnitude lower than that of good TE materials, indicating the bad TE properties of NbP.…”
Section: Resultsmentioning
confidence: 99%
“…Both at low and high fields, N xy peaks near 136 K. Furthermore, it is worth to discuss about that the obtained absolute a xx and a xy at high fields in the polycrystalline sample are smaller than those reported in the single crystals. 22,35 As per our understanding the large difference might be due to three factors: first, the polycrystalline nature of our sample makes the direction of measurement different from that of the single crystals. The grain boundaries in the polycrystalline sample might scatter Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The anomalous Hall effect 49 predicted to exist in time reversal symmetry (TRS) broken WSMs 34,50 has been recently seen in ZrTe 5 45 . The corresponding effect in thermopower, the anomalous Nernst effect in WSM 29,33 has been demonstrated in Cd 3 As 2 42 , NbP 35 and Ti 2 MnX 47 . Chiral magnetic effect, a chiral anomaly induced phenomena 22,23,30 has been reported in ZrTe 5 51 .…”
Section: Introductionmentioning
confidence: 84%
“…This leads to the possibility of several interesting transport phenomena in isotropic and tilted WSMs [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] . Several of these have also been experimentally demonstrated 5,7,[35][36][37][38][39][40][41][42][43][44][45][46][47][48] . For instance, negative magnetoresistivity (MR) 21,24 has been observed in several WSM candidates including the TaAs family 37,38,44 and in WSMs induced magnetically from three dimensional Dirac semimetals 5,7,40 .…”
Section: Introductionmentioning
confidence: 99%
“…[41]. In the case of Weyl materials with a broken time-reversal (TR) symmetry, it was found that, in addition to the usual magnetic-field-dependent Nernst effect, which was recently measured in NbP [42], there is also an anomalous Nernst response [41]. Similarly to the anomalous Hall effect, the anomalous Nernst effect is determined by a nonzero chiral shift.…”
Section: Introductionmentioning
confidence: 96%